2017
DOI: 10.3349/ymj.2017.58.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Palonosetron vs. Ramosetron for the Prevention of Postoperative Nausea and Vomiting: A Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeThis study was designed as a meta-analysis of randomized controlled trials (RCTs) that included the comparison of palonosetron and ramosetron for postoperative nausea and vomiting (PONV) prophylaxis.Materials and MethodsA systematic search was conducted for the PubMed, EMBASE, Web of Science, CENTRAL, KoreaMed, and Google Scholar databases (PROSPERO protocol number CRD42015026009). Primary outcomes were the incidences of postoperative nausea (PON) and postoperative vomiting (POV) during the first 48 hrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A recent meta-analysis showed that palonosetron provided better prophylaxis of early (0-6 h) and late (6-24 h) postoperative nausea, as well as late (6-24 h) postoperative vomiting, compared with ondansetron 19 . In another meta-analysis, palonosetron was more effective in preventing postoperative vomiting than ramosetron during the delayed period (24-48 h) and in females and after laparoscopic surgery 20 . This delayed period is especially important in patients receiving opioid-based IV-PCA because continuous infusion of opioids could cumulatively influence PONV in a dose-related 21 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent meta-analysis showed that palonosetron provided better prophylaxis of early (0-6 h) and late (6-24 h) postoperative nausea, as well as late (6-24 h) postoperative vomiting, compared with ondansetron 19 . In another meta-analysis, palonosetron was more effective in preventing postoperative vomiting than ramosetron during the delayed period (24-48 h) and in females and after laparoscopic surgery 20 . This delayed period is especially important in patients receiving opioid-based IV-PCA because continuous infusion of opioids could cumulatively influence PONV in a dose-related 21 .…”
Section: Discussionmentioning
confidence: 96%
“…Although we found that palonosetron-dexamethasone reduced the incidence of PONV and the incidence and severity of nausea during the 48-h postoperative period compared with palonosetron alone, it did not affect vomiting. As palonosetron has more antiemetic than antinauseant efficacy, the main effect of dexamethasone may have been preventing nausea 20 , 22 . Furthermore, adding palonosetron to the IV-PCA in all patients potentially influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…Palonosetron has a specific ternary ring moiety attached to the quinuclidine ring, therefore can bind more tightly to the receptor and multiple palonosetron molecules bind to a single receptor [ 20 ]. This allosteric binding and positive cooperativity, which are structurally distinct from the first-generation drugs, lead to effective treatment [ 21 ]. Prolonged duration of action of the palonosetron (approximately 40 h, 4-10-fold longer compared to first-generation antagonists) is due to palonosetron-triggered receptor internalization [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Kim et al . 148 failed to find a difference between palonosetron and ramosetron in patients undergoing any type of elective surgery involving general or regional anesthesia.…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 99%